(untitled) (Theatrum historiae, 2012)
This article that is based upon the book of accounts, inventories and correspondence deals with princess Barbora Sanguszkowa (1718–1791), very well educated widow after Pawol Karol Sanguszko and a «muse» of one Polish salon. The author presents her as a propagator of French life style in Poland of 18 century. She analyses everyday life in her residences in Warsaw, Gdańsk and on the countryside. She focuses mainly on eating and table culture and shows how the princess refused Polish tradition and prefered the French one. The author also concerns herself with Sanguszkowa´s servants.